Completing the WTO accession negotiations : issues and challenges. - YANG, Yongheng (1999)
Outlines the importance of WTO applicants in the global economy. Discusses the major economic issues in admitting transition economies to the WTO. Using a global general equilibrium model, examines some of these issues especially the impact of trade liberalisation resulting from WTO accession by these economies. Provides a case study in China's WTO accession.